The Mathematical Simulation Compared to Operations a Small Distributed Photovoltaic Power Plant in a Distribution System - Boonthienthong, Manat; Ngamprasert, Papon; Rugthaicharoencheep, Nattachote (RMUTP Research Journal Sciences and Technology, 2021)
This paper presents a mathematical simulation to compared to operations a small distributed photovoltaic power plant in the distribution system. Practices transmission of electric power by small, distributed solar energy With the PVSyst and IEC 61724 mathematical modeling programs, the main objective was to study the % performance ratio photovoltaic power plants 5.95 MWp connected in the distribution system of the Provincial Electricity Authority, voltage level 22 kV. Therefore, this paper is presented as a mathematical simulation compared to operations a small distributed photovoltaic power plant in a distribution system. The results of the study show that the operation of small distributed solar power plants increases the efficiency to be able to produce the maximum electricity and continuously. The system was able to produce the highest power of 8,954.9 MWh/year and had an average annual efficiency ratio of 77.84%, receiving the highest solar radiation intensity and the highest annual total energy output of approximately 1,837 kWh/m2.